2012
DOI: 10.1002/pssc.201200248
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical characterization of extended defects in silicon mono‐cast material

Abstract: Mono‐cast Si growth is currently a very promising approach to optimize the cost per watt in the production of PV devices, simultaneously increasing the installed energy/m2 ratio. However, due to the novelty of this growth approach, the material properties have not yet been studied in detail. In this work, by combining PL imaging with electrical characterization techniques (LBIC and EBIC), both the large scale and the local properties of the wafers grown from mono‐cast Si ingots have been analyzed. PL imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tsoutsouva et al 53 confirmed that sub‐GBs are the major sources for the development of dislocation cascades and clusters and also reported that the impurities such as N, O, and C preferentially precipitated along sub‐GBs, as shown in Figure 13. Moralejo et al 55 found that impurities were inhomogeneously distributed at the sub‐GBs and the impurity decorated sub‐GBs showed stronger recombination activities compared with “clean” sub‐GBs.…”
Section: Defects In Cast Mono‐like Silicon and Methods To Suppress Themmentioning
confidence: 99%
“…Tsoutsouva et al 53 confirmed that sub‐GBs are the major sources for the development of dislocation cascades and clusters and also reported that the impurities such as N, O, and C preferentially precipitated along sub‐GBs, as shown in Figure 13. Moralejo et al 55 found that impurities were inhomogeneously distributed at the sub‐GBs and the impurity decorated sub‐GBs showed stronger recombination activities compared with “clean” sub‐GBs.…”
Section: Defects In Cast Mono‐like Silicon and Methods To Suppress Themmentioning
confidence: 99%
“…9) It has been reported that sub-GBs in QSC silicon, originating from lattice mismatch between adjacent seeds, can severely degrade the solar cell performances. [10][11][12][13][14][15][16][17] It was found that the misorientation of such sub-GBs in QSC silicon is usually smaller than 3°, 10) which belong to small-angle (SA) GBs. Up to now, substantial research efforts have been devoted to the investigation on the recombination activity of SA GBs.…”
mentioning
confidence: 99%